O cuidar na ação do formador de professores - Marquezano, Viviane Laperuta (2008)
The main purpose of this investigation was to identify what is the point of view that the pedagogical analysts have about caring in its all dimensions: to care, care of the pupil, care of the teacher, being cared and to take care of yourself. These analysts are the responsible for teacher s professional development at SESI s education System, placed in Sao Paulo. The aim of this research was to broaden this vision of caring, that permit us to amplify the dimensions of specialized care in the Analysts action, moreover, reflect on its importance. Data have been collected from individual interviews with ten volunteers analysts at their workplace. The interviewers are responsible for the sixth to ninth grade, when considering nine years education. The data analysis was supported by Henri Wallon s theory of development. According to Wallon care about somebody is to be aware of they well being, taking the responsibility of this action. Caring involves the other and me relationship and keeps changing while the stage of child s development progress. The surroundings must ensure a developmental environment. The specialized care of the analysts should be intentional, planned and shared. This research pinpoints the directress for both pedagogical analysts and managers of SESI s education system with the intention to improve the quality of development of the analysts and, consequently the teachers professional performance